LEVEL OF PHYSICAL FITNESS OF PARTICIPANTS OF SESI – ATHLETE OF THE FUTURE PROJECT IN THE CITY OF SANTA CRUZ DO SUL/RS (Fiep Bulletin - online, 2015)
The present study aims to access the body composition as an indicator of physical fitness related to the health of subjects admitted in the PAF and the physical fitness related to the motor performance of the same subjects using the protocol of tests PROESP-BR (2012). The sample consisted of 88 male subjects, with ages between 9 and 14. Analyzing the results of the participants, for the variable of BMI most participants aged 9 (53.85%) and 13 (41.67%) were classified in risk. It is perceived in the speed test a lower performance of participants aged 9 (84.62%) and 14 (62.5%), being classified as weak. In the variable of lower limbs explosive power, the worst results were found at the ages of 9 (76.92%), 13 (50%) and 14 (50%) and classified as weak. In the agility test the worst performance was of participants at the age of 9 where 69.23% were classified as weak and 23.08% as reasonable, followed by participants aged between 13 and 12 with 50% and 31.58% respectively, both classified as weak. It is concluded that the intervention provided by SESI Athlete of the Future besides enabling a better planning and an appropriate intervention in all motor aspects, will allow through sports practice the proper development of components of physical and motor skills, which will lead to improvements in the lifestyle and sports performance of the participants.
Keywords: Physical fitness; health; motor performance.